A full component recovery process for waste lithium batteries

The waste lithium batteries are separated and recycled through the full wet process, which solves the problems of dust pollution, resource waste and environmental pollution in the existing technology, and realizes efficient recycling and environmental protection processes for various components of lithium batteries.

CN119786783APending Publication Date: 2025-04-08HEFEI GUOXUAN CIRCULATION TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411827014.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing lithium battery recycling process has problems such as dust pollution, resource waste and environmental pollution, and the process is cumbersome, energy consumption is large, and operating costs are high.

Method used

The waste lithium batteries are separated and recycled by a full wet process, including charged crushing, low-temperature volatility, hydraulic sorting, wet screening, high-temperature pyrolysis and flotation, etc., to avoid dust generation and achieve efficient recycling of each component.

Benefits of technology

It effectively avoids dust pollution, reduces resource waste and environmental pollution, reduces energy consumption and operating costs, and realizes efficient recycling of various components of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786783A_ABST
    Figure CN119786783A_ABST
Patent Text Reader

Abstract

The present invention discloses a full component recovery process of waste lithium batteries, including: subjecting waste lithium batteries to charged crushing treatment to obtain crushed materials; subjecting the crushed materials to low-temperature volatilization treatment to obtain low-temperature volatilization materials; subjecting the low-temperature volatilization materials to hydraulic sorting treatment to obtain floating materials and bottom-sinking materials; subjecting the floating materials to wet screening treatment, subjecting the bottom-sinking materials to vibration screening treatment, combining the floating materials and the bottom-sinking materials and subjecting them to high-temperature pyrolysis treatment to obtain pyrolysis materials; subjecting the pyrolysis materials to flotation treatment, graphite is floated out, and flotation precipitates are obtained; subjecting the flotation precipitates to vibration screening treatment, and copper foil, aluminum foil and lithium iron phosphate are screened out respectively. The present invention completely uses a wet process to separate and recycle the components of lithium batteries, which reduces and avoids the generation of dust while also solving the problems of resource waste and environmental pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium battery recycling, and in particular relates to a full-component recycling process for waste lithium batteries. Background Art

[0002] Lithium batteries have advantages such as good cycle performance, high energy density, and stable safety performance, making them an ideal energy source for promoting economic development in the 21st century. As the mainstream power of new energy vehicles, lithium batteries have a service life of about 5-8 years. Therefore, as vehicles are continuously put into use and time passes, power batteries gradually enter the retirement period, resulting in a considerable amount of retirement.

[0003] Starting from 2022, my country's power batteries will gradually enter the large-scale retirement period, and the retirement volume will be about 24GWh in 2023. According to the forecast of China Automotive Strategy and Policy Research Center of China Automotive Technology and Research Center, the retirement volume of power batteries will exceed 30GWh in 2025, exceed 80GWh in 2027, and exceed 100GWh in 2028. In the face of the upcoming large-scale retirement period of power batteries in my country, it is crucial to properly handle waste power batteries.

[0004] The existing lithium battery recycling process generally includes discharge → crushing → low-temperature volatilization → sorting → high-temperature pyrolysis → screening. The common screening processes mainly include: screening out aluminum shells and diaphragms through wind selection, stripping positive and negative electrode active materials and current collectors using a stripping granulator, screening out copper powder and aluminum powder using a specific gravity screen, and separating copper particles and aluminum particles using color sorting. These processes are all carried out in an open environment, so it is inevitable that dust will appear in the environment, causing dust pollution and affecting the health of workers.

[0005] Chinese patent CN109524739A discloses a waste lithium battery recycling process, which is separated by a cyclone separator, sorted by an airflow sorter, and dusted by a pulse dust collector. When filtering dust, the pulse dust collector needs to pump air into the dust collector, then filter it through a bag, and finally discharge the purified air. The lithium battery recycling process disclosed in this patent is relatively cumbersome and consumes a lot of energy. In addition, it has the disadvantages of high operating costs and noise pollution. Summary of the invention

[0006] Based on the above technical problems, the present invention provides a full-component recycling process for waste lithium batteries, which completely uses a wet process to separate and recycle the components of lithium batteries, reducing and avoiding dust generation while also solving problems such as resource waste and environmental pollution.

[0007] The present invention proposes a full component recovery process for waste lithium batteries, comprising the following steps:

[0008] S1. The waste lithium battery is subjected to charged crushing treatment, and the aluminum shell, diaphragm, positive and negative electrode sheets are dispersed to obtain crushed materials;

[0009] S2, subjecting the crushed material to low-temperature volatilization treatment, wherein the electrolyte volatilizes to obtain a low-temperature volatilized material;

[0010] S3, hydraulically separating the low-temperature volatile materials, wherein the diaphragm, graphite and part of the lithium iron phosphate powder float on the water surface to obtain floating materials; the aluminum shell, positive and negative electrode sheets, copper foil, aluminum foil and part of the lithium iron phosphate powder sink to the bottom to obtain sinking materials;

[0011] S4, wet screening the floating material to screen out the diaphragm and obtain the remaining floating material; vibrating screening the bottom material to screen out the aluminum shell and obtain the remaining bottom material;

[0012] S5, combining the remaining floating material and the remaining sinking material and performing high-temperature pyrolysis treatment, so that the binder is cracked and ineffective, and a pyrolysis material is obtained;

[0013] S6, flotation treatment of the pyrolysis material, graphite is floated out, and flotation precipitate is obtained;

[0014] S7, subjecting the flotation precipitate to vibration screening treatment, and copper foil, aluminum foil and lithium iron phosphate are screened out respectively.

[0015] In the present invention, the waste lithium iron phosphate battery is disassembled by shearing and crushing, and then enters a low-temperature volatilization rotary kiln, and its electrolyte is dried under low temperature, and then the materials are directly transferred to a water tank for hydraulic sorting. Due to the difference in density, the diaphragm, graphite and part of the lithium iron phosphate powder float on the water surface, and the aluminum shell, positive and negative electrode sheets, copper foil, positive and negative current collectors of the aluminum foil and most of the lithium iron phosphate powder sink to the bottom. A vibrating screen is set near the bottom of the water tank, and the aluminum shell, positive and negative electrode sheets, copper foil, positive and negative current collectors of the aluminum foil and most of the lithium iron phosphate powder are screened out according to the difference in particle size and hardness. The lithium iron phosphate powder sinks to the bottom of the tank, and the sediment at the bottom of the tank is collected. The diaphragm, graphite and part of the lithium iron phosphate powder are transferred to another water tank. A vibrating screen that can move up and down is set near the water surface to screen out the diaphragm, and the diaphragm is rinsed with clean water to wash off the powder attached to the diaphragm, collect the floating objects, and transfer the sediment at the bottom of the tank and the floating objects to a high-temperature rotary kiln. The binder is ineffective under the action of high temperature, and then it is transferred to the flotation tank to float out the graphite. The sediment at the bottom of the flotation tank is collected and the copper foil and aluminum foil are screened out. The sediment at the bottom of the collected water tank is the lithium iron phosphate powder.

[0016] In the present invention, since the battery materials do not need to go through dry screening or wind sorting processes, they can directly enter the hydraulic sorting process, which can effectively avoid the dust of the extreme powder. In addition, since the lithium compounds and graphite powder in the battery are both conductors and combustibles, if the powder dust is generated during the sorting process and adheres to the electrical switch for a long time, it is easy to cause electrical short circuits, ignition and spontaneous combustion, which poses a safety hazard.

[0017] Preferably, in step S1, the live crushing process is carried out in a battery crusher, the oxygen content in the battery crusher is lower than 1%, and the particle size of the material after crushing is 30-50 mm.

[0018] Preferably, in step S2, the low-temperature volatilization treatment is carried out in a low-temperature rotary kiln, the low-temperature volatilization treatment temperature is 120-200° C., and the time is 0.5-2 h.

[0019] Preferably, in step S3, the hydraulic separation process is to add the low-temperature volatile material into a water tank for stirring and separation.

[0020] Preferably, in step S4, the wet screening treatment is to screen the floating material in water through a vibrating screen with a pore size of 4-6 mm; the vibration screening treatment is to screen the bottom material through a vibrating screen with a pore size of 25-30 mm.

[0021] Preferably, in step S5, the high temperature pyrolysis treatment is carried out in a high temperature rotary kiln, the high temperature pyrolysis treatment temperature is 400-600° C., and the time is 1-2 hours.

[0022] Preferably, in step S6, the flotation is to mix the pyrolysis material with water and place it in a flotation tank for slurry adjustment, and then sequentially add a cationic cyclodextrin polymer, a collector and a frother, and then perform a flotation operation to obtain graphite and precipitate;

[0023] Preferably, the stirring rate of the slurry adjustment treatment is 1500-2000 r / min, and the time is 3-5 min.

[0024] Preferably, the cationic cyclodextrin polymer is obtained by copolymerization of acryloyl-β-cyclodextrin, methacryloyloxyethyltrimethylammonium chloride and methacrylate;

[0025] Preferably, the mass ratio of acryloyl-β-cyclodextrin, methacryloyloxyethyltrimethylammonium chloride and methacrylate is 1:0.05-0.1:1-2;

[0026] Preferably, the added amount of the acryloyl-β-cyclodextrin is 100-200 g / t.

[0027] In the present invention, when a cationic cyclodextrin polymer is used for treatment, the positively charged cationic cyclodextrin polymer can be selectively adsorbed on the negatively charged graphite surface. On the one hand, the adsorption of the cationic cyclodextrin polymer on graphite inhibits the spontaneous hydrophobic flocculation of graphite, thereby ensuring its flotation effect; on the other hand, the β-cyclodextrin cavity structure present in the cationic cyclodextrin polymer can well adsorb collectors such as n-dodecane, thereby ensuring that the collectors are effectively spread on the graphite surface, further promoting the floating of graphite, thereby achieving effective separation of graphite negative electrode materials.

[0028] Preferably, the collector is at least one of n-dodecane, kerosene, diesel or fatty acid, and the foaming agent is at least one of sec-octanol, terpineol or MIBC;

[0029] Preferably, the collector is added in an amount of 50-150 g / t, and the foaming agent is added in an amount of 50-150 g / t.

[0030] Preferably, in step S7, the aperture of the vibration screening treatment is 4-6 mm.

[0031] Compared with the prior art, the present invention has the following technical effects:

[0032] The present invention adopts hydraulic sorting instead of dry screening or wind separation, which can eliminate the phenomenon of dust from extreme powder during the sorting process. The entire recovery process does not need to use organic solvents or chemical methods. The separation medium used is only water, and subsequent treatment is convenient. The positive and negative electrode current collectors and diaphragms can be separated and recovered by physical methods, which effectively solves the problems of resource waste and environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The present invention is a flowchart of the full component recovery process of waste lithium batteries. DETAILED DESCRIPTION

[0034] Hereinafter, the present invention will describe the technical solution in detail through specific embodiments, but it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.

[0035] Example 1

[0036] Reference Figure 1 This embodiment proposes a full component recovery process for waste lithium batteries, comprising the following steps:

[0037] (1) Putting the waste lithium iron phosphate battery into a battery crusher, sealing it and filling it with nitrogen for protection, controlling the oxygen content in the battery crusher to be less than 1%, and shearing and crushing the charged waste lithium iron phosphate battery, so that the aluminum shell, diaphragm, positive and negative electrode sheets are fully dispersed, and the average particle size of the crushed material is 30 mm;

[0038] (2) The crushed material is transferred to a low-temperature volatilization rotary kiln, sealed and filled with nitrogen for protection, the temperature is controlled at 160°C, the time is 1 hour, and the electrolyte is volatilized;

[0039] (3) transferring the materials after the volatilization of the above electrolyte to a first water tank filled with water, and after rapid stirring and separation, the diaphragm, graphite and part of the lithium iron phosphate powder float on the water surface, and the aluminum shell, positive and negative electrode sheets, copper foil, aluminum foil and part of the lithium iron phosphate powder sink to the bottom;

[0040] (4) A vibrating screen with a mesh size of 28 mm is set near the bottom of the first water tank. The bottom materials in the first water tank are vibrated and screened to screen out the aluminum shell and the sediment at the bottom of the tank; the floating materials in the first water tank are transferred to the second water tank filled with water, and a vibrating screen that can move up and down is set near the water surface of the second water tank. The mesh size is 5 mm, and the vibrating screen is moved upward and rinsed with clean water to screen out the diaphragm and floating materials on the tank;

[0041] (5) The sediment at the bottom of the tank and the floating material on the top of the tank are placed in a high-temperature rotary kiln, which is sealed and filled with nitrogen for protection. The temperature is controlled to be 500°C for 1.5 hours, and the binder, residual electrolyte and diaphragm in the positive and negative electrode sheets are cracked into CO2 and H2O;

[0042] (6) The above cracked material was placed in a flotation tank and water was added in an amount of 250 g / L for slurry preparation. The stirring rate was 2000 rpm and the slurry preparation time was 4 min. First, 150 g / t of cationic cyclodextrin polymer was added for slurry preparation for 3 min, and then 100 g / t of kerosene was added for slurry preparation for 3 min. Then, 80 g / t of MIBC was added for slurry preparation for 2 min. The flotation operation was performed. The flotation time was 3 min and the aeration volume was 0.2 m 3 / min, graphite is separated as flotation foam;

[0043] The above cationic cyclodextrin polymer is prepared by referring to the following method:

[0044] β-cyclodextrin is added to N,N-dimethylformamide, and then triethylamine is added in an amount of 50 wt% of the mass of β-cyclodextrin, and acryloyl chloride is added in an amount of 50 wt% of the mass of β-cyclodextrin under nitrogen conditions, and the reaction is carried out at room temperature for 1 hour, followed by filtering and distillation to obtain acryloyl-β-cyclodextrin; the acryloyl-β-cyclodextrin, methacryloyloxyethyltrimethylammonium chloride and methyl methacrylate are added to water in a mass ratio of 1:0.07:1.5, and ammonium persulfate in an amount of 0.05 wt% of the mass of acryloyl-β-cyclodextrin and sodium bisulfite in an amount of 0.15 wt% of the mass of acryloyl-β-cyclodextrin are added under nitrogen conditions, and the reaction is carried out at 50°C for 12 hours, and the reaction is carried out after filtering, washing and drying to obtain the cationic cyclodextrin polymer.

[0045] (7) The sediment at the bottom of the flotation tank is collected and put into a third water tank filled with water. A vibrating screen with a sieve hole diameter of 5 mm is set near the bottom of the third water tank. After vibration screening, the copper foil and aluminum foil are screened out. The sediment at the bottom of the collected water tank is lithium iron phosphate powder.

[0046] Comparative Example 1

[0047] This comparative example proposes a full component recovery process for waste lithium batteries, which is the same as the operation in the embodiment, except that the addition of the cationic cyclodextrin polymer is omitted in step (6).

[0048] The technical indicators for recycling each component of waste lithium batteries are shown in Table 1:

[0049] Table 1 shows the recovery rates of various components of the waste lithium iron phosphate batteries described in Example 1 and Comparative Example 1

[0050] sample Example 1 Comparative Example 1 Copper foil recovery rate (%) 99.1 98.8 Aluminum foil recovery rate (%) 99.2 98.6 Graphite recovery rate (%) 97.9 92.4 Graphite grade (%) 98.3 97.1 Lithium iron phosphate recovery rate (%) 97.1 89.8 Lithium iron phosphate grade (%) 97.2 95.3

[0051] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A full component recovery process for waste lithium batteries, characterized in that: The steps include: S1. The waste lithium battery is subjected to charged crushing treatment, and the aluminum shell, diaphragm, positive and negative electrode sheets are dispersed to obtain crushed materials; S2, subjecting the crushed material to low-temperature volatilization treatment, wherein the electrolyte volatilizes to obtain a low-temperature volatilized material; S3, hydraulically separating the low-temperature volatile materials, wherein the diaphragm, graphite and part of the lithium iron phosphate powder float on the water surface to obtain floating materials; the aluminum shell, positive and negative electrode sheets, copper foil, aluminum foil and part of the lithium iron phosphate powder sink to the bottom to obtain sinking materials; S4, wet screening the floating material to screen out the diaphragm and obtain the remaining floating material; vibrating screening the bottom material to screen out the aluminum shell and obtain the remaining bottom material; S5, combining the remaining floating material and the remaining sinking material and performing high-temperature pyrolysis treatment, so that the binder is cracked and ineffective, and a pyrolysis material is obtained; S6, flotation treatment of the pyrolysis material, graphite is floated out, and flotation precipitate is obtained; S7, subjecting the flotation precipitate to vibration screening treatment, and copper foil, aluminum foil and lithium iron phosphate are screened out respectively.

2. The full component recovery process of waste lithium batteries according to claim 1, characterized in that: In step S1, the charged crushing process is carried out in a battery crusher, the oxygen content in the battery crusher is less than 1%, and the particle size of the material after crushing is 30-50mm.

3. The full component recovery process of waste lithium batteries according to claim 1 or 2, characterized in that: In step S2, the low-temperature volatilization treatment is carried out in a low-temperature rotary kiln at a temperature of 120-200°C for a time of 0.5-2h.

4. The full component recovery process of waste lithium batteries according to any one of claims 1 to 3, characterized in that: In step S3, the hydraulic separation process is to add the low-temperature volatile material into a water tank for stirring and separation.

5. The full component recovery process of waste lithium batteries according to any one of claims 1 to 4, characterized in that: In step S4, the wet screening treatment is to screen the floating material in water through a vibrating screen with a pore size of 4-6 mm; the vibration screening treatment is to screen the bottom material through a vibrating screen with a pore size of 25-30 mm.

6. The full component recovery process of waste lithium batteries according to any one of claims 1 to 5, characterized in that: In step S5, the high temperature pyrolysis treatment is carried out in a high temperature rotary kiln, the high temperature pyrolysis treatment temperature is 400-600°C, and the time is 1-2h.

7. The full component recovery process of waste lithium batteries according to any one of claims 1 to 6, characterized in that: In step S6, the flotation is to mix the pyrolysis material with water and place it in a flotation tank for slurry treatment, and then add cationic cyclodextrin polymer, collector and frother in sequence, and then perform flotation operation to obtain graphite and precipitate; Preferably, the stirring rate of the slurry adjustment treatment is 1500-2000 r / min, and the time is 3-5 min.

8. The full component recovery process of waste lithium batteries according to claim 7, characterized in that: The cationic cyclodextrin polymer is obtained by copolymerization of acryloyl-β-cyclodextrin, methacryloyloxyethyl trimethylammonium chloride and methacrylate; Preferably, the weight ratio of the acryloyl-β-cyclodextrin, methacryloyloxyethyltrimethylammonium chloride and methacrylate is 1:0.05-0.1:1-2; Preferably, the added amount of the acryloyl-β-cyclodextrin is 100-200 g / t.

9. The full component recovery process of waste lithium batteries according to claim 7 or 8, characterized in that: The collector is at least one of n-dodecane, kerosene, diesel or fatty acid, and the foaming agent is at least one of octanol, terpineol or MIBC; Preferably, the collector is added in an amount of 50-150 g / t, and the foaming agent is added in an amount of 50-150 g / t.

10. The full component recovery process of waste lithium batteries according to any one of claims 1 to 9, characterized in that: In step S7, the aperture of the vibration screening treatment is 4-6 mm.

Citation Information

Patent Citations

  • Waste lithium battery recycling process

    CN109524739A